Body Mass Index and Its Relationship to Performance in the Snatch Lift among Female Weightlifters of the Iraqi National Weightlifting Team - Saud Karim; Ayham Saleh (Universitas Negeri Jakarta, 2025)
ABSTRACT The problem addressed in this research stems from the noticeable variance in the performance of female weightlifters during certain lifts in the sport of weightlifting. This variance affects the consistency of achieving the required outcomes in some physical abilities and motor skills, such as the snatch and clean & jerk lifts. One possible cause of this inconsistency is the presence of excess body weight that is not beneficial for performance, particularly in practical training sessions. Possessing good physical and motor fitness is a critical factor in the educational and athletic development process for athletes engaged in various sports activities. By managing and controlling BMI, athletes can maintain an appropriate athletic physique. The research aims to identify the level of performance in the snatch lift in Olympic weightlifting and to determine the nature of the correlation between performance outcomes and the Body Mass Index (BMI). The hypothesis of this work is that there is a statistically significant correlation between performance in the snatch lift and Body Mass Index. The researchers employed the descriptive method using survey and correlational research techniques. The study population was deliberately selected and consisted of female athletes from the Iraqi national weightlifting team. The BMI values for the sample were calculated using the standard BMI formula. The main experiment was conducted over two days. On the first day, the sample was assembled in one of the halls of the Rose Resort in Shaqlawa, Erbil, with the support of an assisting team. On the second day, the snatch lift test was conducted. After completing the BMI measurements and performance tests, the data were statistically analyzed to determine the nature of the relationships among the studied variables and to draw relevant conclusions. Keywords: Body Mass Index (BMI), Performance, Snatch Lift ABSTRAK Permasalahan yang dibahas dalam penelitian ini berasal dari perbedaan nyata dalam performa atlet angkat besi wanita pada angkatan tertentu dalam olahraga angkat besi. Varians ini mempengaruhi konsistensi pencapaian hasil yang diperlukan dalam beberapa kemampuan fisik dan keterampilan motorik, seperti angkatan jerk dan clean & jerk. Salah satu kemungkinan penyebab ketidakkonsistenan ini adalah adanya kelebihan berat badan yang tidak bermanfaat bagi performa, khususnya pada sesi latihan praktik. Memiliki kebugaran jasmani dan motorik yang baik merupakan faktor penting dalam proses pendidikan dan pengembangan atletik bagi atlet yang melakukan berbagai kegiatan olahraga. Dengan mengelola dan mengendalikan BMI, atlet dapat mempertahankan fisik atletik yang sesuai. Penelitian ini bertujuan untuk mengetahui tingkat performa angkatan angkatan angkat besi olimpiade dan mengetahui sifat hubungan antara hasil performa dengan Indeks Massa Tubuh (IMT). Hipotesis dari penelitian ini adalah terdapat korelasi yang signifikan secara statistik antara kinerja dalam angkatan angkatan dan Indeks Massa Tubuh. Peneliti menggunakan metode deskriptif dengan menggunakan teknik penelitian survei dan korelasional. Populasi penelitian sengaja dipilih dan terdiri dari atlet putri timnas angkat besi Irak. Nilai BMI sampel dihitung menggunakan rumus BMI standar. Percobaan utama dilakukan selama dua hari. Pada hari pertama, sampel dikumpulkan di salah satu aula Rose Resort di Shaqlawa, Erbil, dengan dukungan tim pendamping. Pada hari kedua dilakukan uji angkatan grab. Setelah menyelesaikan pengukuran BMI dan tes kinerja, data dianalisis secara statistik untuk menentukan sifat hubungan antar variabel yang diteliti dan untuk menarik kesimpulan yang relevan. Kata Kunci: Indeks Massa Tubuh (IMT), Performa, Snatch Lift